Going the extra mile: Effort by workers and job-seekers - Matthias S. Hertweck; Vivien Lewis; Stefania Villa (Deutsche Bundesbank, 2019)
We introduce two types of effort into an otherwise standard labor search model to examine indeterminacy and sunspot equilibria. Variable labor effort gives rise to increasing returns to hours in production. This makes workers more valuable and contributes to self-fulfilling profit expectations, raising the likelihood of indeterminacy. Variable search effort makes workers search more intensively in a tighter labor market, which alleviates congestion and reduces the likelihood of indeterminacy. Indeterminacy disappears completely when vacancy posting costs are replaced with hiring costs.
Keywords: E23; E24; E32; E64; E71; 330; determinacy; effort; hours; labor market frictions; search intensity